Initial care of maxillofacial polytrauma patients: evaluation, therapeutic management and prevention - Denia Morales Navarro; Dadonim Vila Morales (Editorial Ciencias Médicas, 2015)
Introduction: maxillofacial fractures require emergency treatment by highly qualified personnel. Complications may occur which may cause the death of the patient. Objective: carry out a bibliographic review about the care of maxillofacial polytrauma patients, highlighting the following aspects of advanced trauma life support: management of neurological deficit, exposure and temperature control, annexes to primary assessment, secondary assessment, definitive treatment, associated injuries, multidisciplinary trauma team, maxillofacial traumas with distinctive characteristics, conditions influencing trauma management and prevention. Methods: a bibliographic review was conducted from December 2014 to January 2015. The evaluation included high impact journals from the Web of Sciences (39 journals), as well as one Cuban journal and five books. The databases MEDLINE, PubMed and SciELO were consulted, using the search terms "maxillofacial trauma", "advanced trauma life support", "secondary survey", "associated injuries", "multidisciplinary trauma team", "prevention", and their Spanish counterparts. The review included papers in English and Spanish, preferably published the last five years. Of the 141 papers obtained, the reviewers selected the 51 which approached the study topics in a more comprehensive manner. Data analysis and integration: analysis of the representativeness of papers in scientific journals revealed that 5.9 % corresponded to the Journal of Craniomaxillofacial Surgery. Conclusions: it is indispensable for emergency maxillofacial surgeons to be able to recognize, diagnose and determine the basic management of maxillofacial trauma. Lack of a diagnosis or inappropriate management may lead to the loss of functions and the development of secondary deformities difficult to correct in the future. Such correction could also lead to disappointing results which may risk the patient's life.